Clostridioides difficile Infection in Children: A 5-Year Multicenter Retrospective Study - Buonsenso, Danilo; Graffeo, Rosalia; Pata, Davide; Valentini, Piero; Palumbo, Carla; Masucci, Luca; Ruggiero, Antonio; Attinà, Giorgio; Onori, Manuela; Lancella, Laura; Lucignano, Barbara; Giuseppe, Martina Di; et al. (Frontiers in Pediatrics, 2022)
While there are numerous data regarding C. difficile infection (CDI) in adults, the literature on the pediatric population is scarce. Therefore, we performed a five-year retrospective study in two referral centers in Rome, Italy. 359 patients tested for CDI were enrolled: 87 resulted positive and 272 negative. CDI-children had a higher number of previous day-hospital admissions (p 0.024), hospitalizations (p 0.001), and total hospital admissions (p 0.008). Chronic comorbidities were more frequent in the CDI-group (66.7% vs 33.3%). Previous use of proton-pump inibitors was not associated with CDI and, among the antibiotics, only fluoroquinolones were significantly associated with CDI. Also, CDI children were more frequently exposed to antibiotics during the episode of hospitalization when children were tested. Our study provided an updated clinical, epidemiological and risk-factors analyses of children with CDI compared with a control group of children tested negative. Further prospective studies could better define risk factors and preventive methods.